Prematurity and Low Birth Weight did not Correlate with Anti-Toxoplasma gondii Maternal Serum Profiles – a Brazilian Report - Fochi, Mariana Machado Lemos (PLoS One, 2015)
Gestational Toxoplasma gondii infection is considered a major risk factor for miscarriage, prematurity and low birth weight in animals. However, studies focusing on this topic in humans are scarce. The objective of this study is to determine whether anti-Toxoplasma gondii maternal serum profiles correlate prematurity and low birth weight in humans. The study examined 213 pregnant women seen at the High-Risk Pregnancy Hospital de Base, São José do Rio Preto, São Paulo, Brazil. All serological profiles (IgM-/IgG+; IgM-/IgG-; IgM+/IgG+) were determined by ELISA commercial kits. Maternal age, gestational age and weight of the newborn at birth were collected and recorded in the Statement of Live Birth. Prematurity was defined as gestational age <37 weeks and low birth weight ≤ 2499 grams. The t-test was used to compare values (p < 0.05). The mean maternal age was 27.6±6.6 years. Overall, 56.3% (120/213) of the women studied were IgM-/IgG+, 36.2% (77/213) were IgM-/IgG- and 7.5% (16/213) were IgM+/IgG+. The average age of the women with serological profile IgM+/IgG+ (22.3±3.9 years) was different from women with the profile IgM-/IgG+ (27.9±6.7 years, p = 0.0011) and IgM-/IgG- (27.9±6.4 years, p = 0.0012). There was no statistically significant difference between the different serological profiles in relation to prematurity (p = 0.6742) and low birth weight (p = 0.7186). The results showed that prematurity and low birth weight did not correlate with anti-Toxoplasma gondii maternal serum profiles.